Enhancing Job Stability In Organizations Through Talent Management Practices - Djouahra Moufida (جامعة الوادي University of Eloued, 2024)
In today's era, talent management has emerged as a pivotal functional strategy for organizations. It focuses on unique competencies and exceptional individuals, regarded as the cornerstone of excellence and innovation. Hence, we have undertaken a study to examine this matter and explore the implementation of talent management within Algerian organizations. This includes elucidating the connection between talent management and the job stability of the workforce, following the identification of job stability indicators for Algerian employees. The findings of this study reveal that talent management practices need to be improved within Algerian organizations. Furthermore, they suggest a correlation between talent management and job stability from the employees' perspective. This correlation is observed through guiding and developing employees, as well as creating a conducive environment that fosters job retention and continuous performance enhancement.
Keywords: Talent; Talent management; job stability; job replacement; job security.